(untitled) (Res Medica, 2014)
The term "mugging" has come to be accepted as synonymous with the type of damage which is inflicted by thugs on members of the community. In fact it is the act of attacking from behind or seizing an individual by the throat. To "assault" is to attack violently but this need not be entirely physical and may indeed be at least in part verbal, as for example in an argument. Regrettably the incidence of both is increasing year by year, and not infrequently may endanger life. The circumstances relating to muggings and assault are many, but fall essentially into two groups — the provoked attack and that which is unprovoked. There tend to be three distinct patterns of attack — "man-to-man" contact, that which falls into the category of "gang warfare" in which several individuals attack another group, while gang assaults on individuals are also constantly in the common press. Young people require avenues of expression and if this is improperly provided for, or inadequately controlled, it can lead to violence. Every citizen has a responsibility to the community in which he or she lives and there can be no doubt that they can often discourage such aspects of life as juvenile delinquency and violence by providing facilities and amenities designed to combat such socially unacceptable behavioural patterns. Indiscreet use of the tongue, facial muscles of expression, and digital signs may individually or collectively predispose to evoking physical response from others. Understanding of these precipitating factors and conscious effort to avoid them by whatever means are available will obviously reduce the number of cases of assault. Only a small proportion of such cases reach either the courts or the hospitals and it can be assumed that those which do are of the more serious type.